Analysis of SnO2|WO3 Heterocontact Properties during the Detection of Hydrogen Sulphide - Patrycja Suchorska-Woźniak; Olga Rac; Marta Fiedot; Helena Teterycz (Sensors, 2014)
The main objective of the paper was the analysis of the properties of SnO2|WO3 heterocontact as well as the determination of its response to 50 ppm of hydrogen sulphide. It was noticed that the sensitivity of the sensor being tested to hydrogen sulphide depended significantly on the polarization direction. When its parameters were compared with those of sensors the gas-sensitive layer of which was made only from one type of metal oxide, a high impact of the heterocontact on the electric charge transport was noticed. The value of the activation energy of the electric conductivity is clearly dependent on the polarization direction. A mechanism of physicochemical processes occurring in a planar sensor with a heterocontact was suggested, and three areas differing in the width of depleted layer, where the inter-phase boundary of SnO2|WO3 had the most essential impact on the parameters of the sensor being tested, were distinguished and described.